Analisis Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Di RH SOQ - Asih Ahistasari; Aprisa Rian Histiarini; Nicolaus Yulio Sarfunin (Metode : Jurnal Teknik Industri, 2023)
This study aims to find out how much influence the factors of service quality have on customer satisfaction in RH SOQ. The method used is a quantitative method. Data were collected through observation, interviews, dissemination of questionnaires, documentation, literature studies and RH SOQ sales data. The sample in this study was 93 consumers, with sampling using accidental sampling. Data analysis using multiple linear regression. The results of the coefficient of determination analysis (R2) showed that the influence of variables in the study was 74% and the remaining 26% was influenced by other factors outside this study. Partial testing (t) shows that the variables that have a significant influence are concern, assurance and reliability, while for direct evidence and responsiveness it has no significant effect. The results of simultaneous testing (f) showed that the five variables of service quality in this study had an effect on consumer satisfaction in RH SOQ. This research is expected to be a consideration in decision making for RH SOQ in improving the quality of its services.